2020
DOI: 10.1371/journal.pone.0234509
|View full text |Cite
|
Sign up to set email alerts
|

Electroactivity of polyphenols in sweet sorghum (Sorghum bicolor (L.) Moench) cultivars

Abstract: Polyphenols and other potential health-promoting components of sorghum ( Sorghum bicolor (L.) Moench) drove its recent growth in the U.S. consumer food industry. Linear sweep (cyclic voltammetry, CV) and differential (cyclic differential pulse) voltammetry methods were developed to detect target polyphenols and amino acids in sweet sorghum juice without interference from the dominant secondary (trans-aconitic acid) and primary (sucrose) metabolites. Of 24 cultivars investigated, No.5 Gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
(92 reference statements)
1
6
0
Order By: Relevance
“…Correlations among the various chemical traits of sorghum stem juice were previously reported for the 2015 data (Uchimiya and Knoll 2019b) and the 2017 data (Uchimiya and Knoll 2020). In general, the individual sugars, total sugars, Brix, trans-aconitic acid, and TOC were all positively correlated with one another.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Correlations among the various chemical traits of sorghum stem juice were previously reported for the 2015 data (Uchimiya and Knoll 2019b) and the 2017 data (Uchimiya and Knoll 2020). In general, the individual sugars, total sugars, Brix, trans-aconitic acid, and TOC were all positively correlated with one another.…”
Section: Discussionsupporting
confidence: 54%
“…Electrochemical parameters also showed correlations with aphid damage or aphid days in the 2017-1 and 2017-2 environments. A higher E pa value indicates electrochemically more recalcitrant structure of electron-donating (reductant) components in sorghum juice (Uchimiya and Knoll 2020). The negative correlation between E pa and aphid damage rating suggests multiple chemical pathways against aphids that include polyphenolic antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Gil Zapata [ 27 ] reported that variety L 97-128 had less than half the aconitic acid in tops/leaves when compared with cultivars LCP 85-384 and HoCP 91-555. Among the cultivars, HoCP 96-540, HoCP 04-838, HoCP 09-804, and L 01-299; HoCP 04-838 had significantly more trans -aconitic acid in the sugarcane juice (0.17%) when compared to the other cultivars [ 101 , 102 ], while HoCP 09-804 had more cis -aconitic acid than the others [ 102 ]. When a commercial process was developed for the recovery of aconitic acid from sugarcane streams, others noted that the sugarcane varieties were not grown for their high aconitic acid content but could be cultivated if so desired, at the expense of sucrose [ 99 ].…”
Section: Aconitic Acid In Sugar Cane and Sweet Sorghum And Its Recoverymentioning
confidence: 99%
“…(a) E h –pH diagram of sweet sorghum juice collected from 3 year (2015–2017) field experiments (symbols); values were obtained from the literature ,,, and are closest to catecholic semiquinone radical-forming quercetin . Reduction of model quinone (anthraquinon-2,6-disulfonate) to hydroquinone shifts the fluorescence peak to a higher emission wavelength (black arrow; adapted with permission from ref .…”
Section: Function Of Semiquinone Radicals Through Pcet Pathwaysmentioning
confidence: 99%
“…Figure presents an E h –pH diagram for one-electron half-reactions against the standard hydrogen electrode relevant to sorghum: tryptophan (to form indole radical), tyrosine (phenoxyl radical), quercetin (radical of catechol in B ring), and riboflavin (semiquinone) . Those reference structures are compared against the E h –pH values of sweet sorghum juice collected over 3 years. ,,, Filled symbols in Figure represent mean ± SD for intrinsic E h and pH values of 173 ( n ) sweet sorghum juice samples collected from the field experiment in 2017 and analogous values for 2016 ( n = 67) , and 2015 ( n = 199) …”
Section: Performance Evaluation Of Redox-active Phytochemicals In Agr...mentioning
confidence: 99%